TRANSPLANTASI SEL PUNCA HEMATOPOIETIK AUTOLOGOUS (AUTOLOGOUS HEMATOPOIETIC STEM CELL TRANSPLANTATION) PADA MULTIPLE SCLEROSIS - Elmiraz Takbirani (2021)
Multiple sclerosis (MS) is an autoimmune disease that can potentially paralyze the brain and spinal cord. The immune system attacks the protective sheath of nerves (myelin) and causes permanent damage to nerves. No drug plays a role in providing long-term remission in MS. Stem cell-based therapy is a promising therapy to repair and replace damaged body cells. Autologous hematopoietic stem cell transplantation (AHSCT) is a cell-based therapy that can reset the immune system. The efficacy of this therapy for long-term remission and safety is not yet fully known. In addition, the choice of transplant regimen and patient indications that affect the results of AHSCT is not known with certainty. A systematic review is needed that discusses the efficacy and safety of AHSCT comprehensively. The literature search was conducted from June to August 2021 via Pubmed and Google Scholar. The literature was selected using the PRISMA-P method, resulting in 13 studies according to the inclusion and exclusion criteria. AHSCT has good efficacy in providing long-term remission, especially in MS patients with failure of available disease-modifying therapy. Patients with the Remitting Relapsing MS type showed better results than the other types. Younger age, less history of previous immunotherapy, and lower baseline Expanded Disability Status Scale scores indicated better outcomes. The BCNU, Etoposide, Arabinosylcytosine, Melphalan (BEAM) regimen is the first choice because it provides better results and safety than high-intensity regimens. The safety of AHSCT therapy is high, with a mortality number of 13 cases of 694 samples and treatable side effects.